Interns: Mentoring and Counseling on the Software Development Process - Rizdania, Rizdania; Riono, Sapto Hadi; Rakhmawati, Puji Utami; Darmayanti, Rani (CV. BImbingan Belajar Assyfa, 2023)
The Digital Transformation Services Internship Program at PT Arkatama Multi Solusindo aims to provide opportunities for intern students to develop themselves through direct experience in real projects. With a comprehensive learning approach, interns are given the flexibility to choose positions according to their interests, such as UI/UX designer, Web Developer, and others. This program not only focuses on developing technical skills but also emphasises moral education and professional ethics. Intern students will be involved in prototyping and follow the development process from planning to implementation. The results of their work are documented through logbooks and final reports, building a valuable portfolio. The internship is carried out on-site according to health protocols at PT Arkatama Multi Solusindo, which focuses on digital transformation in various sectors. Services provided include application development, IT Training, and Digital Marketing Services.